Diagnostic urethrocystoscopy: A five-year review of indications and findings in a tertiary hospital in Nigeria - Abdullahi M; Alhassan SU (Ibom Medical Journal, 2022)
Background: Urethrocystoscopy is defined as endoscopic visualization of the urethra and the urinary bladder for the purpose of diagnosis or treatment of diseases of the lower urinary tract. Objective: To study the indications, diagnosis and complications of diagnostic urethrocystoscopy in our hospital.